Pengaruh Struktur Organisasi dan Kepemimpinan pada Kinerja Pegawai PT Bumitama Gunajaya Agro - Juniarti, Atty Tri (Jurnal Trikonomika, 2009)
This study examined the phenomenon of employee performance at PT Bumitama Gunajaya Agro in Jakarta. The purposes of this study are to analyze the influence of organizational structure and leadership toward the employee performance. The research method used were descriptive and verificative, and analysis methoe used the multiple regression, multiple correlation and determination method. This study shows that the organizational structure and leadership has significant influence toward employee performance, but partially leadership also identifies dominant variables to influence the employee performance.